(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
Climate change and its adverse effects on human beings present a global challenge. As a Least Developed Country (LDC), characterized by mountainous terrain, and socio-economic vulnerability, Nepal is particularly at risk. It is imperative for Nepal to develop a comprehensive understanding to cope with the human rights implications of climate change, and to establish mechanisms for redressing harm, risk, and damage to its population. This paper discusses the urgent need to adopt a climate justice-oriented approach to respond to the deteriorating human rights violations resulting from climate change and its impact. Although limited studies have been conducted in Nepal that explicitly examine the overall human rights dimensions of climate change, the latest available information and sources indicate that rampant and increasing violations of human rights are occurring and that there may be more serious concerns about encroachments on human rights in future days. Similarly, the impact and consequences of climate change on human rights is highly unpredictable in terms of harm, risk, and long-term damage. Thus, through a desk review of existing literature, this paper aims to highlight the need for a comprehensive climate justice approach to human rights. Nevertheless, climate justice is a comparatively new phenomenon in human rights. However, its necessity is now unavoidable due to the outcomes and impacts of climate change on one of the world’s most vulnerable countries in terms of geographical and other conditions. Thus, it is important to respond to climate justice issues from a multidimensional perspective, integrating legal, policy, environmental and human rights frameworks to ensure a just and inclusive response to the climate crisis.